Investigating factors affecting medical tourists’ behavioural intention of destination for shariah-compliance medical care: the mediating effects of attitude and perceived behavioural control / Amirah Ahmad Suki - Ahmad Suki, Amirah (2019)
Human behaviour studies are widely acknowledged in the social psychology literature among scholars. Predicting consumers’ future purchase behaviours is still a critically important aspect of forecasting and planning for many service providers in the industry. This study intends to determine the influencing factors affecting medical tourists’ intentions towards choosing a preferred destination that provides shariah-compliance healthcare as a result of an increase in travelling demand for Islamic medical practices. The study assesses the robustness of the theory of planned behaviour (TPB) and extends the theory of destination intention behaviour in shariah-compliance medical services. TPB elements include attitude, subjective norm, and behavioural control, with the addition of new constructs, which are knowledge and shariah-compliance, were applied in this study.